The Role of Soft θ-Topological Operators in Characterizing Various Soft Separation Axioms - Zanyar A. Ameen; Tareq M. Al-shami; Abdelwaheb Mhemdi; Mohammed E. El-Shafei (Journal of Mathematics)
This manuscript begins with an introduction to a soft θ-kernel operator. Then, the main properties and connections of this soft topological operator with other known soft topological operators are examined. We show that soft θ-kernel operator is weaker than soft kernel operator but stronger than soft θ-closure. Both soft θ-closure and soft θ-kernel operators are equivalent on soft compact sets. Furthermore, the stated operators are utilized to obtain several new characterizations of soft Ri-topologies and soft Tj-topologies, for i=0,1 and j=0,1,2.